The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1095/biolreprod.103.016113
|View full text |Cite
|
Sign up to set email alerts
|

The Follicle-Deplete Mouse Ovary Produces Androgen1

Abstract: The follicle-depleted postmenopausal ovary is enriched in interstitial cells that produce androgens. This study was designed to cause follicle depletion in mice using the industrial chemical, 4-vinylcyclohexene diepoxide (VCD), and characterize the steroidogenic capacity of cells in the residual ovarian tissue. From a dose-finding study, the optimal daily concentration of VCD was determined to be 160 mg/kg. Female B6C3F(1) immature mice were treated daily with vehicle control or VCD (160 mg kg(-1) day(-1), 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
229
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(240 citation statements)
references
References 50 publications
10
229
0
1
Order By: Relevance
“…The epoxide 4-vinylcyclohexene diepoxide (VCD) has ovarian-specific toxicity and follicle-depleting properties (Hoyer et al 2001;Mayer et al 2002). The administration of VCD by injection or ingestion repeatedly over a period of up to 30 days depletes the ovary of follicles leading to ovarian senescence (Mayer et al 2004;Hu et al 2006). Similarly, repeated oral administration of triptolide, a diterpenoid triepoxide, affects the ovarian function by causing follicular atresia (Xu and Zhao 2010;Liu et al 2011).…”
Section: Other Contraceptivesmentioning
confidence: 99%
“…The epoxide 4-vinylcyclohexene diepoxide (VCD) has ovarian-specific toxicity and follicle-depleting properties (Hoyer et al 2001;Mayer et al 2002). The administration of VCD by injection or ingestion repeatedly over a period of up to 30 days depletes the ovary of follicles leading to ovarian senescence (Mayer et al 2004;Hu et al 2006). Similarly, repeated oral administration of triptolide, a diterpenoid triepoxide, affects the ovarian function by causing follicular atresia (Xu and Zhao 2010;Liu et al 2011).…”
Section: Other Contraceptivesmentioning
confidence: 99%
“…The effects of estrogens on diet-induced atherosclerosis have been studied in atherosclerosis-prone B6 mice as well as in Apoe KO and Ldlr KO mice under hypercholesterolemic conditions (Bourassa et al 1996, Elhage et al 1997a, Hodgin et al 2001, Mayer et al 2005, Tsuda et al 2005, Seli et al 2007, Villablanca et al 2009). In female animals, the study design usually encompassed surgical or pharmacological castration followed by E 2 substitution to assure E 2 concentrations in plasma comparable to those seen in premenopausal women before ovulation (ca.…”
Section: Effects Of Estrogens On Atherosclerosis In Animal Modelsmentioning
confidence: 99%
“…and, once destroyed, no more can be generated.Therefore, exposure to chemicals that target small follicles can impair reproductive function and cause premature menopause in women (Hooser et al, 1994;Mayer et al, 2002Mayer et al, , 2004. If any deviation from the normal small follicle condition is found on routine histopathological examination, it might be an indication of ovarian toxicity, and more precise histopathological examination, including PCNA immunohistochemistry, should be added.…”
Section: Discussionmentioning
confidence: 99%
“…Haas et al (2007) reported that VCD-treated female mice can be used to model infertility in perimenopausal women. Chemicals that deplete ovarian follicles are of toxicological concern because the mammalian ova--tion can result in premature ovarian failure (early menopause in women; Hooser et al, 1994;Mayer et al, 2002Mayer et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%